2022
DOI: 10.1155/2022/8575026
|View full text |Cite|
|
Sign up to set email alerts
|

Anticancer and Cytotoxicity Activity of Native and Modified Black Rice Flour on Colon Cancer Cell Lines

Abstract: This study is intended to evaluate the cytotoxicity of native and dual-modified black rice flour against the colon cancer cell line (HCT116) and mouse embryo cell line (3T3-L1) by using the MTT assay. The modification techniques applied to prepare rice flour samples were enzymatic modification and heat moisture treatment. In this study, the IC50 of native black rice flour and modified black rice flour was 255.78 µg/mL and 340.85 µg/mL, respectively. The result confirms that the native black rice flour has sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…It provides [42]. IC 50 values greater than 50 μg/mL are considered noncytotoxic [42,43]. In this study, the IC 50 values were found to be less than 50 μg/mL for the leaf and stem methanolic extracts of HepG2 cells, which were found to be much than the IC 50 values for L929 cells.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…It provides [42]. IC 50 values greater than 50 μg/mL are considered noncytotoxic [42,43]. In this study, the IC 50 values were found to be less than 50 μg/mL for the leaf and stem methanolic extracts of HepG2 cells, which were found to be much than the IC 50 values for L929 cells.…”
Section: Discussionmentioning
confidence: 59%
“…Te IC 50 value in pharmacological research is generally considered an indicator of a drug's efectiveness at its half-inhibitory concentration. It provides [42]. IC 50 values greater than 50 μg/mL are considered noncytotoxic [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the five phenolic subfractions, the Sub5 exhibited the most remarkable capacity against HepG2, MCF-7, and Caco-2, with average half-maximal inhibitory concentration (IC 50 ) values of 74.42, 95.33, and 82.19 μ g/mL, respectively, for 72 h. The results indicated that active compounds were mainly concentrated in subfraction 5. According to the US National Cancer Institute (NCI) [ 21 ], the Sub5 exhibited moderate cytotoxicity (IC 50 ranged from 21 to 200 μ g/mL), whereas fluorouracil (5-FU) had high cytotoxicity (IC 50 ≤ 4 μ g/mL) against HepG2 and Caco-2 cells with IC 50 values of 2.41 ± 0.08 and 2.05 ± 0.01 μ g/mL, respectively. In contrast, the subfractions did not significantly affect the cell proliferation of normal mouse liver cells FL83B with the highest concentration tested (Figure S1 ), demonstrating that the toxicity of the samples was limited to cancerous cells.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found that unpolished rice contains bioactive chemicals that have positive health effects. For instance, cancer prevention [18] and the avoidance of diabetic problems [19]. Farmers in Thailand's northeast focus on producing Khao-Mao using pre-harvest rice to increase its value.…”
Section: Introductionmentioning
confidence: 99%